DESIGN AND OPTIMIZATION OF SIZE, LOCATION OF OPENING IN A PRESSURE VESSEL CYLINDER AND HEMI SPHERE BY USING ANSYS (International Journal of Engineering Sciences & Management Research, 2017)
A pressure vessel is a closed container designed to hold gases or liquids at a pressure substantially different from the ambient pressure. The main objective of the research work is to optimize the location and size of opening (hole) in a pressure vessel cylinder and hemi sphere dish end using ANSYS. Analysis is performed for three thick-walled cylinders and hemi spheres with internal diameters 20, 25 and 30 cm having 30 cm height (cylinder) and wall thickness of 20 mm. It is observed that as the internal diameter of cylinder increases the Von Misses stress increases. Optimization of hole size is carried out by making holes having diameter of 4, 8, 10, 12, 14, 16 and 20 mm located at center in each of the three cylinders and Hemispheres, and it is observed that initially Von Misses stress decreases and then become constant with hole size. Lastly, optimization of location of hole is carried out by making a 14 mm hole located at 1/16, 1/8, 2/8, 3/8 and 4/8 of cylinder height from top in all the three cylinders, and different angles like 100, 300, 450, 600 & 900 on Hemisphere dish end.